The Effect of Sustainability Reporting on Firm Value with Gender Diversity of The Board of Directors as a Moderator Variable - Finda Mey Silfani; Suwarno Suwarno (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This inquiry examines the Indonesian banking sector from 2021 to 2024 and assesses whether board gender composition affects the financial implications of sustainability reporting. Methodologically, the study leverages SmartPLS 4 to conduct Structural Equation Modeling (SEM). The empirical results indicate that sustainability reporting, when viewed in isolation, does not materially affect corporate market performance. More critically, the analysis identifies a distinct dampening effect: increased gender diversity on boards appears to attenuate the association between sustainability disclosures and firm value. These outcomes lend empirical weight to the ‘over-monitoring’ hypothesis rooted in Agency Theory. From a managerial standpoint, the findings suggest that banking entities must carefully calibrate their disclosure mechanisms; otherwise, markets may misinterpret rigorous board oversight as an impediment to value creation rather than a safeguard.